Avaliação do efeito do extrato etanólico bruto de Harpagophytum procumbens em camundongos infectados com Toxocara canis - Oliveira, Sandra Regina Pereira de (2012)
The Syndrome of Visceral Larva Migrans (VLMS) is a parasitic disease caused by Toxocara canis, one of the most common helminthes in dogs. In the definitive hosts are present in different morphological forms, embryonated eggs, adult males and females. However, in unusual hosts (humans and rodents), present only in stage infective larvae (L3) and do not complete their life cycle. The infection in man occurs by ingestion of embryonated eggs which release in the small intestine infective larvae (L3), which cross the intestinal mucosa and the lymphatic vessels reach the circulation port reaching the lungs and liver. Larvae can still cross the gut wall actively start a process of erratic migration through different host tissues. The main characteristics of this disease in the chronic phase are eosinofilias blood and tissue and high levels of serum IgE. The immune response of host larvae occurs during tissue migration, where the larvae release antigenic products of excretion-secretion (TES) that protect against host reactions. The TES have a fraction of the allergen responsible for stimulating production and release of eosinophils. In this context, the search for new therapeutic tools that promote less damage to individuals affected by increased systemic eosinophil becomes important. In this study, we evaluated the modulatory activity and anti-inflammatory eosinophilia Harpagophytum procumbens against using the model of experimental infection with T. VLMS kennels. Our results showed that the extract of Harpagophytum procumbens has anti-inflammatory effects in reducing eosinophil infiltration in the blood and washed from the peritoneal and bronchoalveolar at different periods analyzed. The antiinflammatory may be due to the ability of the extract Harpagophytum procumbens decrease the production of factors that favor the proliferation and activation of eosinophils (IL-5, IL-4 and IL-13) during 18, established as the peak of eosinophilia. Furthermore, our treatment decreases the expression adhesion molecules, CD11b, CD11c peak of eosinophilia during infection by T. kennels. The CD40 molecule expression by eosinophils seems to favor the survival of leukocytes, however, would require further investigations that contributed to the understanding of the mechanisms by which the extract of H. procumbens can interfere with the migration of eosinophils into the inflammatory site in this model, since this event is characterized as being complex order.